ANTASEDEN CUSTOMER LOYALTY IN AIRLINES DOMESTIC WITH FULL SERVICE - Albert Mandagi (Business and Entrepreneurial Review, 2015)
The purpose of this study was to observe the effect of the company reputation and service quality on customer loyalty through the mediation of the customer satisfaction and customer trust in the domestic airline with full service. This research was conducted through a survey of air passengers with a total sample of 472 respondents in the five international airports in Indonesia.Primary data was collected by the method of random sampling. The method of data analysis to test the hypothesis used Structural Equation Modeling and Multivariate Analysis, by using software processing Analysis of Moment Structure (AMOS) 18.00. The findings in this study is a customer loyalty positively and significantly influenced by the company reputation, service quality, customer satisfaction and customer trust. Customer loyalty is influenced most strongly by customer satisfaction through the mediation of customer trust, while the customer trust is influenced most strongly by service quality through the mediation of customer satisfaction. This study is limited to domestic airline customers or passengers with full service in economy class in Airline PT Garuda Indonesia and PT Batik Air Indonesia. The research activities carried out at the five international airports which have a relatively high flight schedule, which among Soekarno Hatta in Jakarta, Kuala Namu in Meand, Juanda in Surabaya, Ngurah Rai in Denpasar and Sultan Hasanuddin in Makassar. This study provides a theoretical contributions in the form of an alternative model of customer loyalty in the airline industry and provide managerial implications for the management of the airline.